Faculty Opinion towards Information Resources and Services: a Survey of Undergraduate College Libraries in Chitradurga and Challakere Towns - Lohar, Manjunath; Kumbar, Mallinath (Journal of Information and Knowledge, 2013)
The present survey throws light on the information resources and services etc. available in undergraduate college libraries of Chitradurga and Challakere towns. The study covers 10 different types of under graduate colleges. The present survey collected the data from 69 faculties of different disciplines regarding library resources, services, physical facilities and Internet and computerization of library services etc. It is concluded that no library surveyed is not developed as per the UGC norms especially with regard to automation/digitization of library services.